The Prognosis of Two Year Follow up of Burn Intensive Care Unit Patients - Güneş Çobanoğlu Ercan; Hülya Özay; Elif Bombacı; Banu Çevik; Serhan Çolakoğlu (Galenos Yayinevi, 2012)
Objective: The aim of this retrospective study was to determine the prognostic factors at the burn intensive care unit (BICU). Material and Method: We retrospectively evaluated the patients who treated in BICU between December 2008 and November 2010. The relationship between mortality and the parameters such as age, gender, etiology of burn, burn percentage, discharge from BICU or not, discharge from hospital or not, tracheotomy application, inotropic drug support treatment, GCS score, APACHE II score in admission and 24th hour APACHE II score, duration of mechanic ventilation, duration of hospitalization, blood, tissue/wound, trachea and urine culture results, cause of death were analyzed. Results: The avarage age of patients who died in BICU was higher than the discharged ones (p<0.01). There was no significant difference between genders (p>0.05). The etiology of hospitalization to BICU were flame burns (50%), electrical burns (22%), boiling water burns (17%) and others. The overall mortality was 44.8%. The mortality ratio was 100% in patients who had 70% or higher burn percentage. The admission APACHE II scores, 24th hour APACHE II scores and the ratio of the patients who died in BICU were significantly higher than the discharged ones (p<0.01). The mechanic ventilation support duration time of the patients who died in BICU was higher than the patients who discharged from BICU (p>0.01). Also we evaluated the BICU discharged patient readmission to BICU, 28%. Sepsis and the multiple organ dysfunction were the most common causes of death. The relationship between the blood, tissue/wound, trachea, urine cultures positivity and mortality was analyzed but the results were not statistically significant. Despite these results, positivity of tracheal cultures were more in discharged patients than dead ones (p<0.05) whereas positivity of catheter cultures were less (p<0.01). Conclusion: In our study, we found that, the presence of high burn percentage, mechanic ventilation support duration time, inotropic drug support and high 24th hour APACHE II score increase the risk of mortality.